A microfluidic platform to develop a complex organotypic microtissue - Lu, Xiao Guang (2015)
Stem cells have been applied widely in many areas. The critical hindrance is the complexity of stem cell fate decision. There are various kinds of factors influencing the stem cell fate. Among them, ECM and physical factors play essential roles besides the biochemical factors. The applications of Lab on a chip on the stem cell research give much more convenience due to its small size and capability of complex fabrication. Our research focused the ECM components collagen and HA to illustrate certain facts behind stem cell fate decision. Matrix stiffness as a critical physical factor was also considered combined with collagen and HA influence. To hold these experiment factors together, a simple microfluidic device was introduced based on the lab on chip concept. The results showed that Collagen form matrix would be more attachable for cells and have more positive effect on fibroblast differentiation than HA does. In addition, softer surface showed larger number of cells growing and more cell adhesions between cells.